ROLE OF ICT IN WOMEN EMPOWERMENT: A STUDY WITH A FOCUS ON KUDUMBASHREE PROGRAMME IN KERALA STATE OF INDIA - Manoj P. K (International Journal of Information Technology & Computer Sciences Perspectives, 2014)
Proliferation of Information and Communication Technology (ICT) has notably been playing a cardinal role in women empowerment, financial inclusion and poverty alleviation in India in the ongoing regime of economic reforms. ICT has proven to be a vital tool for enhancement of one‘s productivity and hence earnings, reduction of manual efforts, higher standard of living, and above all, quicker and faster alignment with the developments in the rest of the world. In fact, the developmental role of ICT has been more prominent in various Governmental schemes for the empowerment of the women, the poor and other disadvantaged sections of the population. In the above context, with special reference to the case of ̳Kudumbashree‘ – the poverty alleviation programme of the Government of Kerala, this paper makes a look into the role of ICT initiatives in empowering women, the problems and prospects of such initiatives, and finally offers suggestions for meaningful use of ICT for women empowerment and poverty alleviation.